2011
DOI: 10.1038/bmt.2011.126
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of early hospital discharge following autologous blood SCT: medical outcomes and hospital costs

Abstract: We report the first randomized study comparing early hospital discharge with standard hospital-based follow-up after high-dose chemotherapy (HDCT) and PBSCT. Patients aged 18-65 years, with an indication of PBSCT for non-leukemic malignant diseases were randomly assigned between two arms. Arm A consisted of early hospital discharge (HDCT during hospitalization, discharge at day 0, home stay with a caregiver, outpatient clinic follow-up). In arm B patients were followed up as inpatients. In total 131 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 20 publications
2
51
1
4
Order By: Relevance
“…Nevertheless, currently the use of erythorpietin or amifostine remains unclear whether in the inpatient or outpatient setting. Recently, Faucher et al [73] reported the first randomized study comparing EDM with standard inpatient AHPCT on a cohort of 131 patients with non-leukemic malignant diseases. In both arms A and B, HDC and stem cell infusion occurred during the hospital stay.…”
Section: Early-discharge Model (Edm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, currently the use of erythorpietin or amifostine remains unclear whether in the inpatient or outpatient setting. Recently, Faucher et al [73] reported the first randomized study comparing EDM with standard inpatient AHPCT on a cohort of 131 patients with non-leukemic malignant diseases. In both arms A and B, HDC and stem cell infusion occurred during the hospital stay.…”
Section: Early-discharge Model (Edm)mentioning
confidence: 99%
“…The introduction of their mixed inpatient-outpatient transplant program allowed cost savings up to 1672 Euros/patient without any negative impact on patient's outcome. In a French randomized study [73], shifting from inpatient care to early discharge programs allowed cost savings up to 19% in a group of patients who were actually discharged early. However, considering all randomized patients, the program showed a mean cost per patient only 6% inferior as compared with that of the traditional inpatient group.…”
Section: Outpatient Transplant Programs: Cost Analysismentioning
confidence: 99%
“…21 In this study, HDM was used as conditioning in only 30% of the patients, and the study population was extremely heterogeneous.…”
Section: Background Questionsmentioning
confidence: 99%
“…7-9 The significant increase in the waiting lists generated concerns about the appropriate use of health care resources and, over the past years, some studies have investigated the safety, efficacy and potential cost advantages of reducing hospital stay for patients undergoing ASCT. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The ease of administering HDM, the relatively low extra-hematological toxicity and the short period of neutropenia 5,6 make MM patients ideal candidates for outpatient ASCT programs. Standardization of criteria for the outpatient ASCT policy is a relevant goal of the Italian hematology and transplant community and may facilitate comparison of retrospective and prospective data.…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the paper of Faucher et al 1 dealing with a randomized prospective study of early discharge following autologous peripheral SCT (PBSCT).…”
mentioning
confidence: 99%